Efficacy of using pentoxifylline in patients undergoing breast cancer surgery - Dewidar, Samar A.; Mansour, Noha O.; Hamdy, Omar; Elebedy, Dina A.; Soliman, Moetaza M.; Shams, Mohamed E. E. (Frontiers in Pharmacology, 2025)
IntroductionBreast cancer surgery presents several challenges, including postoperative pain, and wound healing complications. Pentoxifylline is a synthetic methylxanthine derivative known for its anti-inflammatory properties and ability to improve microcirculation, decreasing the inflammatory markers as well as restoring the antioxidant status. This study aims to investigate the potential benefits of pentoxifylline in improving pain control and wound healing in patients undergoing mastectomy.MethodsIn a randomized, single-blinded clinical trial, ninety-two breast cancer patients were assigned to receive pentoxifylline or not. The primary outcome was the measurement of postoperative pain level using the Numeric Rating Scale (NRS) at multiple time points within 24 h post-surgery. Secondary outcomes included determining the time till wound healing and the incidence of postoperative complications.ResultsEighty-eight participants completed this study, 42 patients in the control group while 46 patients in the pentoxifylline group. Patients receiving pentoxifylline demonstrated a significant decrease in NRS scores as compared to the control group (median (IQR) of total area under the curve (AUC) over 24 h were 90 (73.5–102), and 153 (123–168), respectively (P < 0.001)), indicating clinically meaningful reductions in pain intensity. Additionally, pentoxifylline-treated patients experienced faster wound healing, reflected by earlier suture removal (mean ± SD: 15 ± 4.4 days vs. 19.3 ± 6.7 days; respectively (P= 0.001)). The incidence of postoperative complications was significantly lower in the pentoxifylline group (2.2%) compared the control group (19%), P= 0.01. Fewer cases of seroma, wound infection, and wound dehiscence were observed in the pentoxifylline group.ConclusionPreoperative oral administration of pentoxifylline in patients undergoing breast surgery may reduce postoperative pain and improve recovery in those patients. However, further investigations are imperative to validate these findings.Clinical Trial Registrationhttps://clinicaltrials.gov/study/NCT06087237, identifier NCT06087237.